Hybrid Intelligent Systems 15th International Conference HIS 2015 on Hybrid Intelligent Systems, Seoul, South Korea, November 16-18, 2015 - Abraham, Ajith; Han, Sang Yong; Al-Sharhan, Salah A.; Liu, Hongbo (Advances in Intelligent Systems and Computing, 2016)
This book is devoted to the hybridization of intelligent systems which is a promising research field of modern computational intelligence concerned with the development of the next generation of intelligent systems. This Volume contains the papers presented in the Fifteenth International conference on Hybrid Intelligent Systems (HIS 2015) held in Seoul, South Korea during November 16-18, 2015. The 26 papers presented in this Volume were carefully reviewed and selected from 90 paper submissions. The Volume will be a valuable reference to researchers, students and practitioners in the computational intelligence field.